Myanmar Economic Monitor, October 2013 - World Bank (Washington, DC, 2014)
This economic update provides an overview for 2012 and 2013 in Myanmar, years during which the economy continued to accelerate. The main drivers of growth were increased gas production, services, construction, foreign direct investment, and strong commodity exports. Inflation has been on the rise in recent months, but the outlook is positive with the economy projected to grow more. This will be on account of a continued increase in gas production, increased trade, and stronger performance in agriculture. Risks to the outlook include the challenge of maintaining the reform momentum. Externally, a slowdown in Chinese domestic investment and a decline in global commodity prices would hurt commodity exporting countries such as Myanmar. The policy watch section presents a number of planned or recently implemented policy reforms which reflect the country's continuing drive to improve the business environment. A special feature article presents a summary of findings from a recent assessment of Myanmar s Public Financial Management (PFM).